EVALUASI PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL DALAM KURIKULUM MERDEKA DENGAN PENDEKATAN BERORIENTASI PADA TUJUAN TYLER - Tampi Prehadini (Universitas Borneo Tarakan, 2025)
This study aims to evaluate the implementation of Natural and Social Sciences (IPAS) learning at the elementary school level in the context of the Independent Curriculum using RalphTyler'sgoal-orientedevaluationapproach.Theevaluationwascarriedoutonthe achievementoflearningobjectives,thesuitabilityofthelearningprocess,andthe availability of supporting facilities. This study combines the results of field research in the YogyakartaareathathighlightsthechallengesofteachersinimplementingIPASwith Tyler's seven-step evaluation framework. The results of the study indicate that most of the IPAS learning objectives have not been achieved optimally,mainly due to low student reading interest, a learning approach that is still centered on the teacher,and limited learning media. However, teachers show resilience through adaptive and contextual strategies.This evaluation provides important input for improving IPAS learning, increasing facility support, and teacher mentoring policies in the Independent Curriculum.